Novel Coronavirus Disease (COVID-19) and Biologic Therapy for Psoriasis: Successful Recovery in Two Patients After Infection with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) - Nicholas D. Brownstone; Quinn G. Thibodeaux; Vidhatha D. Reddy; Bridget A. Myers; Stephanie Y. Chan; Tina Bhutani; Wilson Liao (Adis, Springer Healthcare, 2020)
Abstract The outbreak of the novel coronavirus known as SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) causing COVID-19 was first reported in late December 2019. Many patients with psoriasis on biologic therapy have asked their medical providers about the effect of biologics on COVID-19. However, it is currently unknown how biologic therapy for psoriasis might impact patients with psoriasis and COVID-19. In this article, we report on the clinical course of two patients on biologic medication for psoriasis who developed COVID-19 and successfully recovered from SARS-CoV-2 infection. Both patients presented with fever and respiratory symptoms, but neither patient required hospitalization. While more research is needed, it is reassuring to know that successful recovery is possible after COVID-19 infection in patients on biologic therapy for psoriasis.